2008
DOI: 10.1253/circj.cj-08-0376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Cerebral Oxygenation During Exercise in Patients With Coronary Artery Disease

Abstract: n resting conditions, complex compensatory mechanisms are believed to adequately regulate blood flow to vital organs, especially to the brain. During exercise, however, the O2 demand of exercising muscles surges to levels 10-15 times higher than that in the resting condition. The blood flow to the exercising muscles increases tremendously to meet this sudden surge in O2 demand, thereby leading to a relative hypoperfusion of other organs. Our group recently studied cerebral oxygenation during exercise using nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…24 Koike et al showed that the decrease in ScO 2 during exercise in patients with coronary artery disease had prognostic effect and was associated with an unfavorable outcome in these patients. 25 Paquet et al observed that baseline ScO 2 was related to LVEF in patients undergoing cardiac surgery and that ScO 2 had an acceptable accuracy to identify left ventricular dysfunction in these patients. 26 The findings of the current study, showing significant correlations between NTproBNP, hsTNT, LVEF, and ScO 2 in a large patient sample, support the concept that ScO 2 is influenced by myocardial function and the performance of the cardiopulmonary system.…”
Section: Discussionmentioning
confidence: 99%
“…24 Koike et al showed that the decrease in ScO 2 during exercise in patients with coronary artery disease had prognostic effect and was associated with an unfavorable outcome in these patients. 25 Paquet et al observed that baseline ScO 2 was related to LVEF in patients undergoing cardiac surgery and that ScO 2 had an acceptable accuracy to identify left ventricular dysfunction in these patients. 26 The findings of the current study, showing significant correlations between NTproBNP, hsTNT, LVEF, and ScO 2 in a large patient sample, support the concept that ScO 2 is influenced by myocardial function and the performance of the cardiopulmonary system.…”
Section: Discussionmentioning
confidence: 99%
“…• O2 decay in recovery is not affected by the exercise duration in an increasing work rate test 12,17 and is easily determined when patients perform at least 50% of maximum exercise. Another advantage for use of T1/2 in recovery as a marker for myocardial ischemia is its sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, speculations on the forehead oxygenation changes based only on the increase and decrease of O2Hb during the exercise are not fully reliable. Considering the potential clinical relevance of their findings, 1 we would suggest they expand the results to include the TOI data as correctly done in their other recent interesting clinical studies. 10,11 …”
Section: To the Editormentioning
confidence: 86%
“…With great pleasure we read the article by Koike et al 1 This is an interesting study investigating, by non-invasive near infrared spectroscopy, 2 the forehead cortical oxy-hemoglobin changes (∆O2Hb) during an incremental symptomlimited cycling exercise test in 344 cardiac patients, and comparing the data with indexes obtained from cardiopulmonary exercise testing. The ∆O2Hb measured from rest to peak exercise was significantly lower in non-survivors than in survivors, suggesting that a decrease in cerebral O2Hb during exercise predicts future cardiovascular events in patients with coronary artery disease.…”
Section: To the Editormentioning
confidence: 99%